2005
DOI: 10.1007/s11373-005-9020-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of a V-type ATPase C subunit gene, Atp6v1c2, during culture of rat lung type II pneumocytes

Abstract: The lung alveolar epithelium consists of type I and type II pneumocytes. In vivo, the type II cell is the progenitor cell from which the type I cell originates. When freshly-isolated type II cells are cultured under conventional conditions they rapidly lose their phenotypic properties and attain characteristics of type I cells. Taking advantage of this transdifferentiation, we sought to identify genes that are differentially expressed during culture of rat type II cells. Using suppression subtractive hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Although these subunits (C1, C2-a, and C2-b) are all structurally different, their functional differences remain unclear. 12,23) Sun-Wada et al showed that V-ATPase containing C2-a or C2-b exhibited a lower K m value or coupling efficiency between ATP hydrolysis and proton transport, suggesting that the C isoforms are involved in the regulation of V-ATPase activity required in different tissues. 18) The human C2 isoform that we expressed using a cellfree protein synthesis system and characterized was the C2-b splice variant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these subunits (C1, C2-a, and C2-b) are all structurally different, their functional differences remain unclear. 12,23) Sun-Wada et al showed that V-ATPase containing C2-a or C2-b exhibited a lower K m value or coupling efficiency between ATP hydrolysis and proton transport, suggesting that the C isoforms are involved in the regulation of V-ATPase activity required in different tissues. 18) The human C2 isoform that we expressed using a cellfree protein synthesis system and characterized was the C2-b splice variant.…”
Section: Discussionmentioning
confidence: 99%
“…Isoform E1 is testis specific and forms a complex with the ubiquitous G1 subunit. Although C2 has 2 splice variants, we expressed and purified only C2-b for our studies, and we assume from previous studies in rats 23) that C2-b is functional during spermatogenesis (human and rat C2-b show 83% sequence identity). The a2 isoform is localized in the Golgi and it is known that the E1 and a2 isoforms are solely responsible for acrosome acidifica-tion in the testis.…”
Section: Quaternary Binding Interaction Among Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…A vacuolar-type H + -ATPase (V-ATPase) C2 subunit gene (Atp6v1c2) was found to be enriched in freshly isolated rat type II cells and almost 90% reduction was observed after 24 h of incubation. In situ hybridization showed that Atp6v1c2 is expressed in both bronchiolar and alveolar lung epithelial cells [8]. Elucidation of differential expression of Atp6v1c2 in type II cells provides information useful in understanding the molecular mechanism during transdifferentiation of alveolar epithelial cells.…”
Section: Increase In Osteopontin Expression In Hypothyroid Micementioning
confidence: 99%
“…9,12 Implied in this notion is mature epithelia, although not multipotent, have some degrees of freedom in reprogramming their chromatin and changing their phenotype in response to new somatic cues ( Figure 1A). Interconversions, for example, have been observed above the gastroesophageal junction, where stratified squamous epithelial cells become columnar, like the intestine, to form Barrett's esophagus 13 ; in type B intercalated cells from the renal collecting duct that change into type A intercalated cells; 14 -16 in type 2 pneumocytes that transdifferentiate into type 1 pneumocytes in the lung; 17,18 in neural retinal cells that morph into pigmented epithelia; 19 in retinal pigmented cells that become lens epithelia; 20,21 in lactotrophs that interconvert to somatotrophs in the pituitary gland; 22 in pancreatic exocrine cells that become hepatocytes; [23][24][25] and in hepatocytes that transdifferentiate into insulin producing cells. 26 -29 All of the drivers underlying these conversions are not understood, but a couple of examples are illustrative.…”
mentioning
confidence: 99%